1990
DOI: 10.2307/3342751
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion on Alcohol Policies

Abstract: We conducted a survey of a probability sample of adult residents in the State of Michigan, assessed public support for various alcohol and drinking-driving policy changes, examined how opinions on various policies clustered, and compared Michigan results with national surveys on these issues. Results showed high levels of public support for raising alcohol excise taxes (82%), prohibiting concurrent sales of alcohol and gasoline (74%), administratively suspending drivers licenses of those over the legal alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…During the past decade, several studies, mainly from the US and Canada, have been conducted on public opinion on alcohol policies [30][31][32][33]. The results of these studies show strong support for alcohol-control policies in the local community.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, several studies, mainly from the US and Canada, have been conducted on public opinion on alcohol policies [30][31][32][33]. The results of these studies show strong support for alcohol-control policies in the local community.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a probability sample of adult residents of Michigan showed that 63% of respondents supported government control to limit the number of alcohol outlets (Wagenaar & Streff, 1990). A similar study of privatization in Ontario, Canada, indicated that the majority (73%) of respondents disagreed with privatization and preferred government control (Anglin et al, 2003).…”
mentioning
confidence: 99%
“…According to Warner (1989), there are 50 million instead of 91 million current smokers, because of consistent and strong anti-smoking efforts since 1964. As previously noted in the research conducted by Wagenaar and Streff (1990), it could be suggested that more stringent alcohol control policies and more strict sanctions against those who drink and drive are endorsed by a sizable majority of the American public. Given the social and economic costs attributable to alcohol and tobacco products, how could anyone argue persuasively to add another drug such as marijuana to that list, especially younger persons?…”
Section: If We Are Really Serious About Drug Preventionmentioning
confidence: 76%
“…For them, alcohol use is "illegal." Wagenaar and Streff (1990), report results from a study of a representative sample of 760 Michigan adults. They found that even 74% of those who drank alcoholic beverages more than once a week were in favor of increasing excise taxes on alcohol and earmarking these funds to combat drinking driving.…”
Section: Legalization: What's In a Name?mentioning
confidence: 99%